Evaluation of the substitution of granule corn by integral sweet potato silage (Ipomoea batata, L.) in a diet for the fattening of male cattle - Ruiloba, M. H.; Maure, J.; Solís, C. (Cuban Journal of Agricultural Science, 2023)
In order to evaluate the substitution of ground granule corn by integral sweet potato silage in a diet for male cattle fattening, a completely randomized design with factorial arrangement 2x2 was used. A total of two substitution levels of the granule corn by integral sweet potato silage, dry basis were studied: 0.0 and 100.0 % and two evaluation periods (28 days each), with previous adaptation of 21 days. The diets were iso-energetic (10.88 MJ ME kg-1 DM) and iso-protein (12.0 % CP). The silage had good organoleptic characteristics. There was not effect of the silage (p > 0.05) on dry matter intake, crude protein and metabolizable energy (2.66 kg, 0.321 and 27.97 MJ 100 kg-1 LWday1). The daily weight gain (p > 0.05), the dry matter conversion and metabolizable energy (p > 0.05), with average of 1.84 kg animal-1 day-1, 6.86 kg and 72.00 MJ kg-1 weight gain , respectively was neither affected. The substitution of 0.0 % showed better crude protein conversion than those of the 100.0 % (0.796 y 0.849 kg kg-1of weight gain) (p < 0.01). The weight in hot carcass was not affected by the silage, with average of 269.4 kg animal-1 (p > 0.05).The feeding cost of the treatment with the silage was 21.4 % lower than those with the ground granule corn. It is concluded that the integral sweet potato silage have viability as competitive alternative for the substitution of the granule corn in fattening diets of male cattle. Key words: silage, sweet potato, substitution level, weight gain, feeding cost